Energy Efficiency Optimization of Milk Homogenizers: A Contribution to the European Green Deal Goals - Samoichuk Kyrylo; Kovalyov Alexandr; Palianychka Nadiia; Hutsol Taras; Komarnitskyi Serhii; Bezaltychna Olena; Kuboń Maciej; Tabor Sylwester; Kukharets Valentyna (Production Engineering Archives)
The modern global milk processing industry involves the use of innovations and optimization of existing industry management methods, which contributes to the realization of sustainable development and energy efficiency. Increasing the energy efficiency of dispersing and homogenizing milk and dairy products can contribute to the practical implementation of the philosophy of the “European Green Deal”. The jet-slot milk homogenizer is one of the most energy-efficient among all types of homogenizers in the dairy industry. The principle of its operation is based on the creation of a maximum speed difference between the fat balls of cream and the flow of skimmed milk. This makes it possible to obtain a high degree of dispersion with high energy efficiency of the process. Reducing the specific energy consumption and finding the optimal parameters of the homogenizer were based on the results of both theoretical and experimental studies and were carried out graphically. The optimization criteria (decreasing specific energy consumption while maintaining high homogenization quality) were chosen to achieve a dispersion of 0.8 μm with minimal energy consumption. The diameter of the confusor is optimized at the point of greatest narrowing. The obtained results indicate that to increase the energy efficiency of homogenization, the parameter values should be within 3.5–4.0 mm. The parameters of the width of the ring gap, the fat content and the speed of the cream are optimized. The results showed that it is possible to reduce the specific energy intensity of the process to values of 0.88–0.92 kWh/t when using cream with a fat content of 33–43%, which should be fed through an annular gap with a width of 0.6–0.8 mm. Optimum values of the cream feed speed were found, which should be equal to 7–11 m/s. The research results are of high practical value for the further development of an energy-efficient industrial model of a jet-slot homogenizer.